Numerical study of film cooling influence on performance of transonic vane cascade - Alameldin, Ahmad M. (AUC Knowledge Fountain, 2014)
Gas turbines are a major contributor to world power generation with applications ranging from electricity production to aircrafts propulsion. Their efficiency is subject to continuous research. A gas turbine's overall efficiency is directly proportional to flow inlet temperature. Various methods are implemented to protect hot gas path components from mainstream flow well above their melting temperature, namely, heat resistant coatings, internal cooling and film cooling. The latter is the subject of this work. A 3-D Computational Fluid Dynamics (CFD) model is solved using ANSYS CFX software and compared to experimental measurements of film cooled transonic vane cascade operating at a Mach number of 0.89; the experimental data used for validation is provided by Heat and Power Technology Department of the Royal Institute of Technology (Kungliga Tekniska HÃƒÂ¶gskolan, KTH) of Stockholm, Sweden. A new approach was used to model the film cooling holes, omitting the need to model both the coolant plenum and cooling tubes, resulting in 180% reduction in grid size and attributed computational cost interpreted in 300% saving in computation time. The new approach was validated on a basic flow problem (flat plate film cooling) and was found to give good agreement with experimental measurements of velocity and temperature at a blowing ratio (BR) of 1 and 2; the experimental data for the flat plate was provided by NASA's Glenn Research Center. The numerical simulation of the cooled vane cascade was compared to experimental measurements for different cooling configurations and different BRs. a) One row on pressure side at BR = 0.8, 0.96 and 2.5. b) Two rows on suction side (location 1) at BR = 0.8, 1.4 and 2.5. c) Two rows on suction side (location 2) at BR = 0.8. And d) Showerhead cooled vane at BR ranges between 1.98 and 5.84. The coolant was applied at the same temperature as the mainstream, to match experimental conditions. A good agreement with the experimental measurements was obtained for exit flow angle, vorticity downstream of the vane, pressure coefficients and aerodynamic loss. The proposed approach of coolant injection modeling is shown to yield reliable results, within the uncertainty of the measurements in most cases. Along with lower computational cost compared to conventional film cooling modeling approach, the new approach is recommended for further analysis for aero and thermal vane cascade flows.